GLOBAL OPTIMIZATION VERY FAST SIMULATED ANNEALING INVERSION FOR THE INTERPRETATION OF GROUNDWATER POTENTIAL - Samsul Bahri; Sanny Virginia Aponno; Zulfiah Zulfiah (JGE (Jurnal Geofisika Eksplorasi), 2022)
This study examines the inversion modelling of one-dimensional Schlumberger configuration resistivity data using the Very Fast Simulated Annealing (VFSA). Detailed identification and mapping of aquifer conditions is very important for the sustainable development of groundwater resources in an area. Vertical electrical sounding (VES) and surface electrical resistivity surveys have proven very useful for studying groundwater due to their simplicity and cost effectiveness. Global optimization inversion method also provides an inversion solution that is not expected to be trapped in a local minimum solution, so that it will get results that are closer to the actual situation. The VFSA method is inspired by phenomena in metallurgy related to the formation of crystals in materials caused by thermodynamic processes. This inversion scheme was tested initially with free noise synthetic data and with noise 5%. Furthermore, the program is applied to field data that has been measured in Ambon City, Maluku, Indonesia. The results of the VFSA inversion on field data obtained four layers consisting of top soil (141.2 ± 0,61 m) with a thickness of 1.43 m, andesite breccia rock (355.90 ± 0.46 m) with a thickness of 4 m, lapilli tuff (93.40 ± 0.31 m) with 30 m thick, then the last is the coarse tuff layer (34.30 ± 0.15 m) which is estimated as an aquifer.